The Flouting of Grice’s Politeness Maxims in Podcast Directive Speech Acts of Dive Studios Channel (The Journal of Educational Development, 2021)
The speaker sometimes expressed their speech act inappropriately then the interlocutors may feel embarrassed or humiliated by the speaker. People who want to maintain good communication can do flouting maxim. The point of this research is to explain the flouting of the Grice Maxims in the Dive Studios Channel Podcast. Besides, this research also tries to show a relation among the flouting of the Grice Maxim. This research is conducted by using a qualitative study based on the theory of the flouting of the Grice maxim (1989). The data are in the form of directive speech acts by speakers and guests in Podcast videos of Dive Studios Channel on Youtube that consist of advice, commands, orders, questions, and requests. The findings showed that there are four types of flouting maxims used by the speakers and guests, namely flouting maxims of quantity, flouting maxims of quality, flouting maxims of relation, and flouting maxims of manner. I also found the relation among the flouting of Grice Maxims in the Podcast such as creating humor, expressing emotions, producing figurative language, and conveying messages. Furthermore, can be concluded that the flouting maxims are the way to make the communication run smoothly and show a great ambiance.